2010
DOI: 10.1152/ajpheart.00372.2010
|View full text |Cite
|
Sign up to set email alerts
|

Sustained suppression of sympathetic activity and arterial pressure during chronic activation of the carotid baroreflex

Abstract: Lohmeier TE, Iliescu R, Dwyer TM, Irwin ED, Cates AW, Rossing MA. Sustained suppression of sympathetic activity and arterial pressure during chronic activation of the carotid baroreflex. Am J Physiol Heart Circ Physiol 299: H402-H409, 2010. First published May 28, 2010; doi:10.1152/ajpheart.00372.2010.-Following sinoaortic denervation, which eliminates arterial baroreceptor input into the brain, there are slowly developing adaptations that abolish initial sympathetic activation and hypertension. In comparison,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 25 publications
8
88
1
Order By: Relevance
“…An increase in the resting activity of the C1 cells and other presympathetic neurons of the RVLM could plausibly contribute to the increased SNA in such diseases (9,78). Chronic baroreceptor stimulation, which presumably decreases the activity of the C1 cells in the conscious state as under anesthesia, produces a sustained AP reduction in experimental animals and in humans with drug-refractory essential hypertension (106). In human heart failure, the overflow of catecholamine metabolites from the brain is enhanced suggesting that the release of CNS norepinephrine, and possibly epinephrine, is elevated (94).…”
Section: C1 Cells and Diseasementioning
confidence: 99%
“…An increase in the resting activity of the C1 cells and other presympathetic neurons of the RVLM could plausibly contribute to the increased SNA in such diseases (9,78). Chronic baroreceptor stimulation, which presumably decreases the activity of the C1 cells in the conscious state as under anesthesia, produces a sustained AP reduction in experimental animals and in humans with drug-refractory essential hypertension (106). In human heart failure, the overflow of catecholamine metabolites from the brain is enhanced suggesting that the release of CNS norepinephrine, and possibly epinephrine, is elevated (94).…”
Section: C1 Cells and Diseasementioning
confidence: 99%
“…10 At the same time, they suggested that renal nerves are not the only mechanism because renal denervation does not abolish sustained reduction in AP during baroreflex activation. 47 While electrical activation of the carotid baroreflex does not seem to disrupt the native baroreflex function, 48 examining the baroreflex equilibrium diagram after baroreflex activation therapy in an animal model of hypertension might provide further information as to…”
Section: Clinical Implicationmentioning
confidence: 99%
“…105 In his original study, Thrasher (2002) showed that unloading of baroreceptors at one carotid sinus (with all other arterial baroreceptors denervated) caused a sustained pressor response lasting up to 3 weeks in conscious dogs. 105 Lohmeier et al 106 electrically stimulated the carotid sinus directly and also showed reductions in arterial pressure for up to 3 weeks. Subsequently, carotid sinus stimulation has been performed in humans with hypertension.…”
Section: Drug-resistant Hypertension-how To Treat?mentioning
confidence: 99%